1995
DOI: 10.1161/01.str.26.11.2154
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Increases Regional Cerebral Blood Flow and Reduces Infarct Size After Experimental Ischemia in a Rat Model

Abstract: The present study suggested that intracarotid administration of bFGF (100 ng) can reduce infarct size after MCA occlusion. It was speculated that the increased CBF in the penumbral areas of MCA may contribute to contraction of infarct size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
6

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 27 publications
2
32
1
6
Order By: Relevance
“…We previously could not demonstrate a significant in vivo decrease in ischemic lesion volumes with basic fibroblast growth factor with a similar study protocol, 44 whereas we could demonstrate a significant effect of the agent at postmortem as several studies had demonstrated before. [45][46][47][48] Using a glycine site antagonist, we obtained a significant postmortem reduction in ischemic lesion size, while in the same study DWI did not show an in vivo effect during a 3.5-hour MRI protocol. 49 With the same drug and with a similar study protocol, others have shown an in vivo lesion reduction by DWI at 6 hours after MCAO, 50 suggesting a late effect.…”
Section: Tatlisumak Et Al April 1998 855mentioning
confidence: 53%
“…We previously could not demonstrate a significant in vivo decrease in ischemic lesion volumes with basic fibroblast growth factor with a similar study protocol, 44 whereas we could demonstrate a significant effect of the agent at postmortem as several studies had demonstrated before. [45][46][47][48] Using a glycine site antagonist, we obtained a significant postmortem reduction in ischemic lesion size, while in the same study DWI did not show an in vivo effect during a 3.5-hour MRI protocol. 49 With the same drug and with a similar study protocol, others have shown an in vivo lesion reduction by DWI at 6 hours after MCAO, 50 suggesting a late effect.…”
Section: Tatlisumak Et Al April 1998 855mentioning
confidence: 53%
“…This may require further investigation because another growth factor, bFGF, has been shown to dilate collaterals in the peri-ischemic zone, even at doses not promoting systemic hypotension, thus increasing blood flow to the penumbral regions. 30 In conclusion, intravenous administration of G-CSF achieved a significant neuroprotective effect in cell culture and after focal cerebral ischemia and was associated with increased STAT3 expression. These effects were probably mediated by interaction with G-CSFR.…”
Section: Physiological Parameter Of G-csf Treated Animals and Controlsmentioning
confidence: 82%
“…For example, in a focal ischemia model in the rat, intravenous administration of bFGF reduced the infarct size. 1,12,22) In models of middle cerebral artery occlusion in rat, treatment with bFGF demonstrated a decrease in infarct size. 22) However, the mechanism of infarct reduction by bFGF remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reduction in infarct size was accompanied by an increased rCBF in the peri-infarct area. 22) Furthermore, bFGF has a potent neurotrophic function 25) and this may cause the therapeutic effect on cerebral infarction. This protective effect may be independent of rCBF increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation